Perbedaan kadar glukosa darah berdasarkan hasil pemeriksaan spektrofotometer dengan glukometer di UPTD Puskesmas Sukajaya Kota Sabang - Farah Fajarna; Safridha Kemala Putri; Nelvi Indah Irayana (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Diabetes Mellitus is a group of metabolic disorders with typical symptoms of hyperglycemia. Blood glucose examination can use a spectrophotometer and a glucometer (Point of Care Test). Although both are used to check blood glucose, these two tools have some differences when viewed from the working principle, the samples used, and their benefits. Both tools have advantages and disadvantages. The cost factor, a spectrophotometer is more expensive and requires more blood and a long time. Compared to glucometers, which are cheaper, easier to use, and have faster results. However, the level of reliability in measuring the value of fasting blood sugar levels is not yet significantly known.Objectives: This study aims to measure the difference in fasting blood sugar levels based on a spectrophotometer examination with a glucometer examination at Sukajaya Health Center, Sabang City.Methods: The analytical descriptive research uses a cross-sectional design. The research was conducted at the Sukajaya Health Center in Sabang City in October 2019. The object of this study was 24 patients. The examination is carried out through a Duplo process to avoid errors. The tools used to check fasting blood sugar levels are Spectrophotometer and Glucometer. Data analysis used non-parametric statistical tests, namely Kruskal Wallis, at 95% CI.Results: The average fasting blood glucose level using a spectrophotometer with repetition twice (Duplo) is 146.83 mg/dl (minimum= 77 mg/dl and maximum= 404 mg/dl). While the average value of fasting blood glucose levels examined using a glucometer is 158,25 mg/dl (minimum = 66 mg/dl and maximum= 424 mg/dl). The results of statistical tests indicate a difference in the average fasting blood glucose levels in patients examined using a spectrophotometer with a glucometer (p= 0,019; p < 0,05) at UPTD Puskesmas Sukajaya Sabang City.Conclusion: Using a glucometer, the results of checking blood glucose levels show a higher value than a spectrophotometer. There are differences in fasting blood sugar levels in patients examined with a spectrophotometer and glucometer.